A multi-method approach to examining consumer intentions to use smart retail technology. (April 2021) - Fazal-e-Hasan, Syed Muhammad; Amrollahi, Alireza; Mortimer, Gary; Adapa, Sujana; Balaji, M S
Abstract: This study examines the antecedents and consequences of customers' intentions to use smart retail technology (SRT), specifically Smart Retail Carts. We propose that perceived novelty, perceived efficacy, perceived compatibility, and perceived risk of SRT determine consumers' intentions to use SRT, which, in turn, influences their shopping value through and interaction with this SRT. Survey responses from 338 actual shoppers with prior experience of SRT were used to test the research model. In addition to structural equation modeling (SEM), the Fuzzy-Set Qualitative Comparative Analysis (fsQCA) technique was used to analyze the data. SEM analysis enabled us to investigate and hypothesize relationships among the above factors, while fsQCA helped develop configurations of factors and find the appropriate target consumers of SRT. The findings posit perceived novelty, perceived efficacy, perceived compatibility, and perceived risk of SRT as antecedents to, and shopping value through SRT and interaction with SRT as consequences of, customers' intentions to use SRT. Moreover, the study found configurations of factors, such as perceived novelty and perceived compatibility, resulted in improved intention to use this form of SRT. The present study offers a better understanding of consumers' intentions to adopt SRT that may help managers to develop adoption strategies for successful implementation of SRT in-store. Highlights: This study examines the antecedents and consequences of customers' intentions to use smart retail technology (SRT). The work employs SEM and fsQCA techniques to add robustness to the research. Perceived novelty, efficacy and compatibility are antecedents to customers' intentions to use SRT. Perceived risk of SRT reduces customers' intentions to use SRT. The study found factors, such as perceived novelty and perceived compatibility, resulted in improved intention to use SRT.